Efectos de variabilidad climática en la planificación de las actividades agrícolas del cultivo del Maíz Amarillo duro variedad marginal 28- tropical, campaña chica, sector Cacatachi- región San Martín. - Ruíz Beteta, Pedro Pablo (2008)
The experiment was developed in the farm of the National University of St Martin Cacatachi District, Province And Region St Martin, with a geographical location: South latitude, 06 ° 25, length west 76 ° 00 ', and an altitude of 328 m.s.n.m, in a clayey soil of texture, with medium availability of elements (N, P, K, Ca Mg). The aim (lens) was: Determines the effect of the climatic variability and its incident in the planning of the agricultural activities of small campaign in the culture (culturing) of maize (corn), in Cacatachi district. The used design was of block Randomized (DBCA), With 3 repetitions and 4 ttos, using 12 experimental units; they were studied 4 epochs of sowing (August, September, October, November) to determine the best adapted month to sow in the small campaign, to the shaded ones I do not apply any type of irrigation to be able to determine the production to the dryness, I use a distancing of sambaed 0. 80 m between rows and 0. 80 m plants respectively. The results show that the treatment T3 obtained a better production since during its phonological stage of development there was sufficient availability of elements as rainfalls radiation, dampness, that's why is for it l determined that the small campaign must sow in October that gave to us a performance (yield) of 3, 55 TM/Ha And that is not very propitious to sow in August and September since it is an drier epoch and likewise in November that has some disadvantages. Likewise it was possible to compare and determine the climatic variability of last 30 years relating to the rainfall and to the average temperature, which in agreement to the obtained in case of the rainfalls there was an increasing of 204, 24 mm in the last 30 years and it tends to continua in increasing on having passed of the years and to disorder the campaigns and productions and in the alive beings. At the same time relating to the average temperature it is possible to observe that in the last 30 years there was an increasing of O, 5° C with tendency to rise and also it wi11 bring serious consequences for the life worldwide.